Pest categorisation of Stegophora ulmea. (19th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health (PLH) performed a pest categorisation of Stegophora ulmea, a well‐defined and distinguishable fungal species of the family Sydowiellaceae. S. ulmea causes a tree disease known as black spot of elm ( Ulmus spp.). The pathogen is reported from North America (native range) and Asia (Far‐East Russia and China), but not from the EU. S. ulmea is regulated in Council Directive 2000/29/EC (Annex IIAI) as a harmful organism whose introduction into the EU is banned on plants of Ulmus L. and Zelkova L., intended for planting, other than seeds. The pathogen has been occasionally intercepted on imported bonsai plants (and then destroyed) in the Netherlands and the UK. It could enter the EU and spread within it via plants for planting (including bonsai) and cut branches. Hosts and favourable climatic conditions are common in the EU. The European native elm species Ulmus glabra and Ulmus laevis were found to be more susceptible to the disease than North American elm species, but information is lacking on Ulmus minor . The disease is rarely fatal, but S. ulmea can cause considerable damage, particularly in wet summers. Reduction of inoculum by the removal of leaf debris and avoiding overhead watering in nurseries can reduce the risk of spread of the pathogen. The main knowledge gaps concern (i) the distribution of the pest in Asian countries, (ii) the relative role of the means of entry/spread and (iii) the potential consequences in mature tree plantations and native woodland. The criteria assessed by the Panel for consideration as potential quarantine pest are met. For regulated non‐quarantine pests, the criterion on the pest presence in the EU is not met.